Multi-channel time-frequency fusion attacks. (27th August 2021) - Cao, Yuchen; Zhou, Yongbin; Zhang, Hailong
Side-channel analysis (SCA) is one of the most powerful attacks against cryptographic implementations. Multi-channel fusion attack (MCFA) which can utilise leakages measured from different side channels is a new type of SCA. Till now, existing MCFAs mainly work in the time domain. This paper take time-frequency joint information into consideration, and proposes time-frequency fusion attacks (TFFA). TFFA can be easily expanded to multi-channel case, and this kind of attack is named multi-channel time-frequency fusion attack (MCTFFA). In comparison to existing MCFAs, TFFA and MCTFFA are more effective. Practical experiments against unprotected AES-128 (implemented on MCU and FPGA) and masked AES-128 (implemented on FPGA) show that proper MCTFFA can reduce the number of traces needed to achieve a success rate of 1 by 23% to 60%, compared to that of MCFA. These improvements can be achieved without overhead in measurement complexity.